Gender Differences in the Relationship Between Sleep Problems and Suicide Attempt in Adolescents - Wan, Yuhui; Xu, Huiqiong; Wang, Shanshan; Boyda, David; Mcfeeters, Danielle; Sun, Ying; Zhang, Shichen; Chen, Ruoling; Tao, Fangbiao (Frontiers in Psychiatry, 2020)
Abstract There are few studies examining which types of sleep problems are independently associated with suicide attempt (SA) and gender difference in adolescents. The aim of the present study was to examine whether specific sleep problems were uniquely associated with suicide attempt in adolescents and explore gender differences in the association. A school-based health survey was conducted in four provinces within China from November 2014 to January 2015. A total of 15,132 students aged 10-21 years completed standard questionnaires assessing 12 month suicide attempt in addition to measures of sleep quality, quantity and sleep beliefs. 5.4% of participants reported a suicide attempt within the last 12 months. After adjustment for sociodemographic variables and psychological symptoms, almost all sleep problems remained significantly associated with a greater endorsement of a suicide attempt. Further adjustment for co-occurring sleep problems revealed that weekday sleep duration (<6h, 8-10h and ≥10h), insomnia (often) and nightmares (sometimes and often) remained independently associated with suicide attempt in boys (p<0.05). However in girls, weekday sleep duration (<6h and ≥10h), weekend sleep duration (<6h), midday nap (0 or 1-2d/week), insomnia (sometimes and often), nightmare (often) and sleep beliefs (high) were independently associated with suicide attempt (p<0.05). Multiple sleep problems are associated with suicide attempt in adolescents, however the relationship varies by gender.